Medication Gaps and Antipsychotic Polypharmacy in Previously Hospitalized Schizophrenia Patients: An Electronic Cohort Study in Three Canadian Provinces - Peters, Evyn; Shamloo, Arash; Lodhi, Rohit J.; Marcoux, Gene; Jackson, Kylie; Halayka, Shawn; Balbuena, Lloyd (Frontiers in Psychiatry, 2022)
Background: Real world evidence about antipsychotics focuses on rehospitalization. Modeling the time course of pharmacotherapy would show patients’ adherence to medications and physicians’ adherence to medication guidelines. We aimed to calculate the cumulative time spent in second generation antipsychotics (SGAs), gaps, antipsychotic polypharmacy, and clozapine in discharged schizophrenia patients. Methods: Hospitalization and pharmacy dispensing data from 2008-2018 in Manitoba, Saskatchewan, and British Columbia were linked and an electronic cohort (N=2,997) was created (mean follow-up: 49 months, SD = 38). Cohort members were required to have a minimum of 6 weeks medicated with aripiprazole, olanzapine, paliperidone, quetiapine, risperidone, or ziprasidone. Results: The multistate model predicted that schizophrenia patients accumulate 44 months in SGA monotherapy, 4 months in polypharmacy, 11 months in medication gaps and 17 days in clozapine over a five-year period. The majority of transitions were between SGA and medication gap. Accumulated time in medication gaps was seven times as much as in clozapine. Each 10% delay in SGA initiation post- discharge was associated with a 2%, 1%, and 6% higher risk for polypharmacy (95% CI: 1.01-1.02), gap (95% CI: 1.01-1.01), and clozapine (95% CI: 1.04-1.08), respectively.